ANALISIS KOHESI DAN KOHERENSI WACANA DALAM BERITA ONLINE BERBAGI PAKET SEMBAKO UNTUK KAUM DHUAFA DI JAWA POS RADAR BOJONEGORO EDISI 11 MEI 2019 - Armala, Suci (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
Cohesion and coherence in discourse play a role in forming a wholeness in the discourse itself, both discourse and writing. One of the written discourses is the news in the Jawa Pos newspaper, which is the distribution of basic food packages breaking the fast of Ramadhan for the poor in the Tuban area held by PT. PJB UBJOM PLTU Tanjung Awar-awar, in this news is thought to contain elements of cohesion and coherence. This study uses a qualitative descriptive approach and discourse analysis techniques. The data obtained contains cohesion and coherence. In this data collection, namely by listening to the news and recording it. The results of this study include grammatical cohesion, lexical cohesion and its coherence. Grammatical cohesion includes reference cohesion, recovery cohesion, release cohesion and liaison cohesion. In addition to cohesion there is also coherence that is like the coherence of the means of purpose, the coherence of reasons for action, the coherence of the meaning of reason and so forth. With the discovery of the use of cohesion and discourse coherence in Jawa Pos news.